EXPLORING THE ART OF CRYSTAL GROWTH: UNVEILING THE SECRETS UNDER VARIED EXTERNAL CONDITIONS - Nasrullaeva Durdonа Bakhromovna; Zaripova Barno Ikramovna (Лучшие интеллектуальные исследования, 2024)
Introduction: Crystals, with their mesmerizing geometries and dazzling beauty, have captivated humanity for centuries. From the quartz in your watch to the diamonds in your jewelry, these ordered arrangements of atoms possess remarkable properties that find applications in diverse fields, ranging from electronics to medicine. However, the journey of crystal growth is not merely about their end utility; it's a fascinating scientific exploration, where the interplay of external conditions shapes their formation. In this article, we delve into the art and science of growing crystals under varied external conditions, unlocking the secrets behind their diverse structures.